KONSELING DENGAN STRATEGI RESTRUKTURISASI KOGNITIF : PENGARUHNYA TERHADAP EFIKASI DIRI PERFORMANSI AKADEMIK MAHASISWA PSIKOLOGI UNIVERSITAS NEGERI MALANG - Septian, Muhammad Rezza; Manuardi, Ardian Renata (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2021)
This research based on the urgency of self efficacy academic performance level in psychology students University State of Malang which has the concept of wrong thinking. This study used one group pretest posttest design with six research subjects, and Wilcoxon test was chosen as data analysis in this study. The results showed that cognitive restructuring strategy in counseling process can improve self efficacy of student academic performance.